2014
DOI: 10.1016/j.virol.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

The identification and characterization of nucleic acid chaperone activity of human enterovirus 71 nonstructural protein 3AB

Abstract: Human enterovirus 71 (EV71) belongs to the genus Enterovirus in the family Picornaviridae and has been recognized as one of the most important pathogens that cause emerging infectious disease. Despite of the importance of EV71, the nonstructural protein 3AB from this virus is little understood for its function during EV71 replication. Here we expressed EV71 3AB protein as recombinant protein in a eukaryotic expression system and uncovered that this protein possesses a nucleic acid helix-destabilizing and stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Interestingly, enterovirus 2C ATPase is not the only RNA remodeling protein encoded by enteroviruses. Previous studies by DeStefano and colleagues showed that poliovirus 3AB is an RNA chaperone [ 42 , 57 ]; moreover, our previous report confirmed that EV71 3AB also contains in vitro RNA chaperone activity [ 58 ]. In addition, poliovirus 3D pol has been reported to display unwindase activity that does not require ATP hydrolysis but does require an RNA chain elongation reaction [ 59 ].…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, enterovirus 2C ATPase is not the only RNA remodeling protein encoded by enteroviruses. Previous studies by DeStefano and colleagues showed that poliovirus 3AB is an RNA chaperone [ 42 , 57 ]; moreover, our previous report confirmed that EV71 3AB also contains in vitro RNA chaperone activity [ 58 ]. In addition, poliovirus 3D pol has been reported to display unwindase activity that does not require ATP hydrolysis but does require an RNA chain elongation reaction [ 59 ].…”
Section: Discussionsupporting
confidence: 63%
“…DeStefano and colleagues have showed that poliovirus protein 3AB possesses properties consistent with classical RNA chaperone proteins, and was able to greatly accelerate the rate of annealing between complementary nucleic acids and destabilize short double-stranded RNA substrates (DeStefano and Titilope, 2006). Moreover, our group has also demonstrated that protein 3AB from EV71 has RNA chaperone activity (Tang et al, 2014). These findings suggest that RNA chaperone activity is a general function of nonstructural protein 3AB in picornaviruses.…”
Section: Coronavirus N Proteinmentioning
confidence: 58%
“…Poliovirus 3AB was the first RNA chaperone described in picornaviruses (DeStefano and Titilope, 2006). Domain organization and disorder prediction analyses showed that poliovirus or EV71 protein 3AB does not contain any intrinsically disordered regions, implying that the entropy transfer mechanism does not apply to enteroviral 3AB (Tang et al, 2014). However, the RNA chaperone activity of 3AB was moderately inhibited by various divalent metallic ions, implying that 3AB remodels RNA molecules through transient ionic interactions with the negatively charged RNA backbone (Woodson, 2010).…”
Section: Coronavirus N Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 3B and the last seven amino acids at the C-terminal of 3A (termed 3B ? 7) possess RNA chaperone activity, and five amino acids, i.e., Lys-80, Phe-82, Phe-85, Tyr-89, and Arg-103, are critical and probably the active sites of 3AB for its RNA chaperone activity (Tang et al 2014). The Golgi resident protein acylcoenzyme A binding domain-containing 3 (ACBD3) promotes EV71 replication by interacting with the 3A protein (Fig.…”
Section: A Proteinmentioning
confidence: 99%